IMPLEMENTASI PEMBELAJARAN AQIDAH AKHLAK DALAM MEMBENTUK KARAKTER ANAK USIA DINI DI PAUD CENDANA PUTIH - Wati, Mirna; Unaeni, Ajeng (As-Sulthan Journal of Education, 2026)
Character education in early childhood forms the basis for holistic human development. While implementing Aqidah Akhlak learning in early childhood education is considered strategic, there is limited empirical evidence on its models and effectiveness in specific contexts. This study analyzes the implementation of Aqidah Akhlak learning and its contribution to character development at Cendana Putih Kindergarten. Using a qualitative single case study design, data were collected through participant observation, semi-structured interviews with five teachers and seven parents, and document analysis. Data were analyzed using the Miles and Huberman (1994) model. Integrated Aqidah Akhlak learning is implemented through value habituation activities, teacher role modeling (uswah), exemplary narratives (qishah), and a supportive environment. This approach significantly shapes children's character, especially in independence, discipline, respect, and responsibility. Collaboration among schools, families, and communities serves as a key reinforcing factor. Contextual and holistic Aqidah Akhlak learning is effective as a foundation for character education in early childhood. The findings recommend developing locally based modules and structured parenting programs for broader application.